2021
DOI: 10.1016/j.jmrt.2021.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Application of green synthesised copper iodide particles on cotton fabric-protective face mask material against COVID-19 pandemic

Abstract: Microorganisms cause variety of diseases that constitutes a severe threat to mankind. Due to the upsurge of many infectious diseases, there is a high requirement and demand for the development of safety products finished with antimicrobial properties. The study involves the antimicrobial activity of natural cotton coated with copper iodide capped with Hibiscus rosa-sinensis L. flower extract (CuI-FE) which is rich in anthocyanin, cyanidine-3-sophoroside by ultrasonication method. The coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Such surfaces resist the entry the virus into human cell by passivation of receptors spikes. For instance, Archana et al [ 80 ] reported about coating of copper iodide on cotton fabrics by ultrasonication method. In this study, copper iodide was synthesized by the use of aqueous extract of Hibiscus flower as a source of reducing, stabilizing and capping agents.…”
Section: Mechanism Behind the Antiviral Efficacy Of Cu Nanoparticles ...mentioning
confidence: 99%
“…Such surfaces resist the entry the virus into human cell by passivation of receptors spikes. For instance, Archana et al [ 80 ] reported about coating of copper iodide on cotton fabrics by ultrasonication method. In this study, copper iodide was synthesized by the use of aqueous extract of Hibiscus flower as a source of reducing, stabilizing and capping agents.…”
Section: Mechanism Behind the Antiviral Efficacy Of Cu Nanoparticles ...mentioning
confidence: 99%
“… FE-CuI NPs engineered cotton mask provides better viral entry inhibition capacity. [154] Deng et al, mRNA incorporated lipid NPs (mRNA- HB 27 -LNPs Antiviral efficacy against corona virus In- vivo study speculated the improved circulating half-life with greater protection against virus after i.v administration of mRNA-HB 27 -LNPs into mice model. [155] Sanna et al, Remdesivir loaded targeted NPs (RDV-TNP-1 Antiviral activity against COVID 19 RDV-TNP-1 showed highest binding propensity to ACE2 receptor with enhanced antiviral efficacy and better biocompatibility.…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 99%
“…For instance, CuI-capped Hibiscus rosa-sinensis L. flower extract (CuI-FE) containing a pentanoic acid and 2-(aminooxy) nanocomposite (NC) coated on cotton fabric shows high tensile strength and elongation (TS 31.58 MPa and EAB 21%, respectively) with the ability to interact with COVID-19 protease (binding energy −80.34 kcal mol −1 ). 26 Aerosol droplets become entrapped and inactivated, and the efficiency of the face mask material was enhanced by assembling the mask barrier in three layers such that the outer two layers contained CuS NPs coated and impregnated onto 20D spandex, 70D nylon, and 75D polyester fibers that are organized in supercoiled and vertical orientations ( Fig. 2 ).…”
Section: Nanostructured Antiviral Filtersmentioning
confidence: 99%